Kongenitální katarakta--růst oka po implantaci PC IOL - Syslová, J; Krásný, J; Kuchynka, P (Ceska a slovenska oftalmologie, 2004)
The authors followed the influence of PC IOL (posterior chamber intraocular lens) implantation in congenital cataract to the growth of the eyeball (six bilateral cataracts and 6 monolateral cataracts). The development of the eye growth was compared to the 6 healthy eyes of patients of this group. The intraocular lens implantation was performed at the age of 1 to 5.5 year, in average at the age of 3 years. The follow up period was 4 to 7 years, mean 6 years. In operated, as well as in non-operated eyes, an equal average growth of the eyeball 0.2 mm per year was detected. All operated eyes were slightly hypermetropized according to the physiological values of growth of healthy eyes. The absolute mean deviation from emmetropia was 1.8 diopters. The author established the suitability of intraocular lens implantation in small children because of positive influence to the growth as well as to the final visual acuity, which ranged from 0.05 to 1.0, mean 0.4.
Keywords: kojenec; Infant; Follow-Up Studies; extrakce katarakty; Cataract Extraction; katarakta; předškolní dítě; Humans; Child, Preschool; lidé; oči; Lens Implantation, Intraocular; Eye; Cataract; následné studie; implantace nitrooční čočky